Disturbed cyclical stretch of endothelial cells promotes nuclear expression of the pro-atherogenic transcription factor NF-kappa B - Pedrigi,RM; Papadimitriou,KI; Kondiboyina,A; Sidhu,S; Chau,J; Patel,MB; Baeriswyl,DC; Drakakis,EM; Krams,R (Annals of Biomedical Engineering, 2016)
Exposure of endothelial cells to low and multidirectional blood flow is known to promote a pro-atherogenic phenotype. The mechanics of the vessel wall is another important mechano-stimulus within the endothelial cell environment, but no study has examined whether changes in the magnitude and direction of cell stretch can be pro-atherogenic. Herein, we developed a custom cell stretching device to replicate the in vivo stretch environment of the endothelial cell and examined whether low and multidirectional stretch promote nuclear translocation of NF-κB. A fluid–structure interaction model of the device demonstrated a nearly uniform strain within the region of cell attachment and a negligible magnitude of shear stress due to cyclical stretching of the cells in media. Compared to normal cyclical stretch, a low magnitude of cyclical stretch or no stretch caused increased expression of nuclear NF-κB (p = 0.09 and p < 0.001, respectively). Multidirectional stretch also promoted significant nuclear NF-κB expression, comparable to the no stretch condition, which was statistically higher than the low (p < 0.001) and normal (p < 0.001) stretch conditions. This is the first study to show that stretch conditions analogous to atherogenic blood flow profiles can similarly promote a pro-atherogenic endothelial cell phenotype, which supports a role for disturbed vessel wall mechanics as a pathological cell stimulus in the development of advanced atherosclerotic plaques.